Semantic Relation of the Football Supporter Names in Indonesia - Mad Yahya; Fachri Hamzah Pangestu (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This article aims to analyze the lingual aspects of Indonesian football supporters’ names due to its potential to unravel the intricate interplay between language, social dynamics, and culture within this community. The data sources are Indonesian football supporters’ names from 28 clubs of the 1st and 2nd 2022/2023 league competitions. The data source is quite representative because these leagues are the two best professional leagues with the largest number of supporters in Indonesia. The authors collected data using note-taking techniques from official club websites, official supporters’ websites, media reports, and supporters’ social media accounts. Moreover, the authors also interviewed supporters from two popular League 1 clubs, PSS Sleman and Persib Bandung. Interviews were conducted to validate the naming of supporters, the language origin, and the diversity of the supporter names. Data analysis was examined by identifying the morpheme elements, categorizing the formation of naming supporters, analyzing the lexical meaning of the names, and categorizing the meaning relation of the semantic markers in the supporters’ names. Based on these findings, the authors identified trends in the semantic relations that are widely used in the naming of Indonesian supporters. The study findings show that the supporters’ names are morphologically formed through abbreviations/acronyms, lexical borrowing, and compounding. Through semantic identification, there are three categories of semantic references in the supporters’ names, namely the origin of the region and club, local culture, and military terms. In these three semantic references, the lexical choices such as mania, extreme, fanatik, brajamusti, and other military terms in the supporters’ names show the tendency of ultras feelings and fanatism of the football fandom.